Parameter optimization for solid fluidization exploitation of natural gas hydrate in South China Sea. Issue 3 (12th August 2021) - Mao, Liangjie; Cai, Mingjie; Liu, Qingyou; Zhang, Ying
Abstract : Purpose: The purpose of this paper is to study the multi-phase flow behaviors in solid fluidization exploitation of natural gas hydrate (NGH) and its effect on the engineering safety. Design/methodology/approach: In this paper, a multi-phase flow model considering the endothermic decomposition of hydrate is established and finite difference method is used to solve the mathematical model. The model is validated by reproducing the field test data of a well in Shenhu Sea area. Besides, optimization of design parameters is presented to ensure engineering safety during the solid fluidization exploitation of NGH in South China Sea. Findings: To ensure the engineering safety during solid fluidization exploitation of marine NGH, taking the test well as an example, a drilling flow rate range of 40–50 L/s, drilling fluid density range of 1.2–1.23 g/cm3 and rate of penetration (ROP) range of 10–20 m/h should be recommended. Besides, pre-cooled drilling fluid is also helpful for inhibiting hydrate decomposition. Originality/value: Systematic research on the effect of multiphase flow behaviors on the engineering safety is scare, especially for the solid fluidization exploitation of NGH in South China Sea. With the growing demand for energy, it is of great significance to ensure the engineering safety before the large-scale extraction of commercial gas from hydrate deposits. The result of this study can provide profound theoretical bases and valuable technical guidance for the commercial solid fluidization exploitation of NGH in South China Sea.